Carbon nanofiber with selectively decorated pt both on inner and outer walls as an efficient electrocatalyst for fuel cell applications - Balan, Beena K.; Unni, SreeKuttan M.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2009)
A novel electrocatalyst, with excellent Pi dispersion oil the inner and outer wall of a carbon nanofiber (CNF) was prepared by a modified polyol process in which both surface tension and polarity characteristics of the medium were properly adjusted to favor solution entry into the tubular region by capillary filling and homogeneous wetting of the inner wall surface by the solvents. The pristine CNF, which possesses an inherently active inner wall surface and inactive outer Wall surface, led to selective Pt deposition along the inner wall, whereas activation of the outer wall with chemical functionalization resulted in excellent dispersion of Pt along both inner and outer walls. Structural and morphological characterizations using high resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD) revealed that when Pt could be dispersed along the inner as well as the Outer walls of CNF, the Pt particle size decreased to almost half as compared to the one With Pt decoration only along a single wall of the Substrate material. Further, electrochemical studies using cyclic voltammetry (CV) and rotating disk electrode (RDE) measurements revealed enhanced methanol oxidation and oxygen reduction properties, respectively. The electrochemical active area obtained for the catalyst with both inner and outer wall Pt decoration wits nearly two times higher than that corresponding to the one with only inner wall Pt decoration. Similarly, the rate constant for the oxygen reduction reaction displayed by this sample was four times higher in comparison with the sample prepared by Utilizing only one wall for Pt decoration.

Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrids for improved supercapacitor performance - Balan, Beena K.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (RSC Advances, 2013)
Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrid electrode material which integrates dual wall decoration and interfacial area tuning for supercapacitor applications has been devised based on a simple approach. This is achieved by decorating RuO2 nanoparticles of size ca. 2-3 nm along the inner and outer walls of a hollow carbon nanofiber (CNF) support (F-20RuO(2)). In the next step, a proton conducting polymer, phosphoric acid doped polybenzimidazole (PBI-BuI), interface is created along the inner and outer surfaces of this material. A 103% increase in the specific capacitance is obtained for RuO2-PBI hybrid material as compared to that of F-20RuO(2) at the optimum level of the polymer wrapping. Apart from the high specific capacitance, the RuO2-PBI hybrid materials exhibit enhanced rate capability and excellent electrochemical stability of 98% retention in the capacitance. Such a remarkably high activity can be primarily attributed to the efficient dispersion of active sites achieved by properly utilizing inner and outer surfaces of CNF. Apart from this, the facile routes for ion transport created as a result of PBI incorporation coupled with excellent interfacial contact between the RuO2 and the electrolyte resulting in the improved utilization of the active material also contribute to the improved activity. In addition to this, the synergistic effects of pseudocapacitive contribution from both the PBI-BuI and RuO2 also contribute to the redefined performance characteristics.